Underdog [videorecording (Blu-Ray)] - Du Chau, Frederik; Belushi, James, 1954-; Barber, Gary; Birnbaum, Roger; Glickman, Jonathan; Polstein, Jay; Piscatella, Joe; Williams, Craig A.; Rifkin, Adam, 1966-; Dinklage, Peter; Warburton, Patrick; Slattery, John, 1962-; et al. (Buena Vista Home Entertainment, 2007)
After an accident in the lab of the maniacal Dr. Barsinister, an ordinary beagle named Shoeshine finds he has some unimaginable powers, along with the ability to speak. Underdog vows to protect the citizens of Capitol City, and one beautiful spaniel named Polly Purebred.